COMMON PEDIATRIC RESPIRATORY INFECTIONS: PREVENTION AND CARE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Common pediatric Respiratory infections in children caused by both viruses and bacteria are major global contributors to illness and death. These conditions involve specific pathophysiological changes, such as immune system activation, inflammation, and shifts in biochemical processes. Examining the underlying biochemical mechanisms helps inform diagnostic methods, treatment plans, and the importance of nursing care. Proper management is essential to enhance recovery and reduce complications in pediatric cases. This review aims to offer a current assessment of the pathophysiology, biochemical features, diagnostic techniques, treatment options, and nursing strategies related to childhood respiratory infections. It emphasizes factors like age-related variations, immune responses, and evidence-based nursing practices. Drawing from clinical research, case studies, and biochemical data, the review presents a thorough summary of the topic. Key areas discussed include infection causes, immune defense mechanisms, biochemical indicators used in diagnosis and monitoring, symptoms, and nursing care approaches. Common triggers include viral agents like respiratory syncytial virus (RSV) and influenza, as well as bacterial pathogens such as Streptococcus pneumoniae. These infections prompt immune reactions marked by the release of inflammatory cytokines and measurable biomarkers including C-reactive protein (CRP) and procalcitonin (PCT). Effective clinical care requires comprehensive nursing support, including maintaining hydration, managing fever, and assisting with breathing. Emotional support and family involvement are also vital for recovery. Pediatric respiratory infections are multifaceted, involving interactions between immune, biochemical, and clinical elements. Knowledge of disease mechanisms and relevant biomarkers supports timely diagnosis and targeted treatment. Nursing care plays a critical role in managing symptoms, ensuring patient comfort, and limiting transmission. Prompt action and holistic care strategies can significantly improve health outcomes for children affected by these infections.